Effect of ignition timing advance on performance of a small producer gas engine - N. Homdoung (2018)
In this work, a small, single cylinder, naturally aspirated, compression ignition engine was modified into a spark ignited (SI) engine where producer gas was used solely as fuel. Experiments were carried out at various engine speeds and loads to study effect of ignition timing adjusted to maximum brake torque (MBT) on overall engine performance. From the tests, it was found that coefficient of variation from representative measurements was in a range of 1. 75-3. 0%. As expected, the performance of the engine was dependent on ignition timing advance. The optimum ignition timing of the small producer gas engine was observed to be between 20° to 25° BTDC at 1100 rpm, and increase with engine speed. Maximum brake mean effective pressure and minimum brake specific fuel consumption rate were 195. 48 kPa, and 0. 93 kg/kWh, respectively, obtained at 1700 rpm on full load. At this condition, brake thermal efficiency of about 19% was achieved. © Research India Publications.